DERIVATIF KEUANGAN, KOMPENSASI EKSEKUTIF, DAN KEPEMILIKAN KELUARGA DALAM KAITANNYA DENGAN AGRESIVITAS PAJAK: PERAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2018–2024 - Ardilan Yusmin; Herman Darwis; Meliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the relationship between financial derivatives, executive compensation, and family ownership on tax aggressiveness with independent commissioners as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange during the 2018–2024 period. This research employs a quantitative approach using secondary data obtained from annual reports and financial statements. The sample was selected using a purposive sampling method based on predetermined criteria. Data were analyzed using panel data regression and Moderated Regression Analysis (MRA) with the assistance of EViews 12 software. The results indicate that financial derivatives and family ownership do not have a significant effect on tax aggressiveness, while executive compensation has a positive effect on tax aggressiveness. Furthermore, independent commissioners are unable to moderate the relationship between financial derivatives and family ownership on tax aggressiveness but are able to moderate the relationship between executive compensation and tax aggressiveness. These findings suggest that managerial incentive factors play a more dominant role in encouraging tax aggressiveness practices than ownership characteristics and the use of derivative instruments. This study contributes to the literature on taxation and corporate governance, particularly regarding the determinants of tax aggressiveness in Indonesian manufacturing companies.